ÐŸÑ€Ð¸Ð¼ÐµÐ½ÐµÐ½Ð¸Ðµ Ñ„Ñ€Ð°ÐºÑ‚Ð°Ð»ÑŒÐ½Ð¾Ð³Ð¾ Ð°Ð½Ð°Ð»Ð¸Ð·Ð° Ð¿Ñ€Ð¸ Ð¾Ñ†ÐµÐ½ÐºÐµ Ð¸Ð·Ð¼ÐµÐ½ÐµÐ½Ð¸Ñ Ð¼Ð°ÐºÑ€Ð¾ÑÑ‚Ñ€ÑƒÐºÑ‚ÑƒÑ€Ñ‹ Ð´ÐµÐ³Ð¸Ð´Ñ€Ð°Ñ‚Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… Ð±Ð¸Ð¾Ð»Ð¾Ð³Ð¸Ñ‡ÐµÑÐºÐ¸Ñ… Ð¶Ð¸Ð´ÐºÐ¾ÑÑ‚ÐµÐ¹ - Marchenko, N. V.; Dyubko, T. S.; Marchenko, V. S.; Belonozhko, A. P.; Linnik, T. P.; Yakovleva, E. A.; Chub, N. N.; Egorov, M. I.; Artemenko, A. B. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2007)
It has been shown that the facies of dehydrated biological fluids (BF) of humans and animals (saliva, blood plasma, sperm plasma, placenta extracts et al.) have the characteristic structure, are sensitive to deriving source and methods, as well as to different types of physical-chemical effects not only in vitro but also in vivo. The method of quantitative description of macrostructural changes of dehydrated BF has been proposed, based on fractal analysis of facies images. The algorithm of software complex for contrasting, morphometry and computation of fractal dimensions for images of the smears for microscopy has been described.Â